1989
DOI: 10.1002/tera.1420390107
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of 3,3‐dimethyl‐1‐phenyltriazene in the rat: Gross malformations including micrognathism

Abstract: 3,3-Dimethyl-1-phenyltriazene (DMPT), an alkylating agent, has been reported to be teratogenic in chickens, mice, and rats. One of the most commonly affected structures is the mandible; however, a complete description and incidence rates of all malformations produced have not been published. Rats were treated on day 12 of gestation (day 0 = sperm in vaginal smear) with a single intraperitoneal injection of 30 mg DMPT/kg. Fetuses were examined on each subsequent day of gestation for external and skeletal abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Early studies of the vascular disruption mechanism involved uterine vascular clamping, which produced abdominal wall, limb, renal, and other defects (Brent and Franklin, 1960). Also, experimental studies of animal models have shown that various hemorrhage‐inducing agents can produce these defects, such as thalidomide (Delahunt and Lassen, 1964; Wilson and Gavan, 1967), triazene (Frank et al, 1989; Louryan et al, 1995; Glineur et al, 1999), cocaine (Webster and Brown‐Woodman, 1990), and salicylates (Warkany and Takacs, 1959; Kimmel et al, 1971; Khera, 1976). In humans, associations have been reported for a variety of vasoactive agents, including thalidomide (Brent and Holmes, 1988), misoprostol (Orioli and Castilla, 2000; Vargas et al, 2000), cigarette smoking (Goldbaum et al, 1990; Haddow et al, 1993; Czeizel et al, 1994; Kallen, 1997a, 1997b; Skelly et al, 2002) cocaine (Hoyme et al, 1990; Addis et al, 2001), aspirin (Kozer et al, 2002), and ibuprofen (Werler et al, 2004).…”
Section: Vascular Disruptionmentioning
confidence: 99%
“…Early studies of the vascular disruption mechanism involved uterine vascular clamping, which produced abdominal wall, limb, renal, and other defects (Brent and Franklin, 1960). Also, experimental studies of animal models have shown that various hemorrhage‐inducing agents can produce these defects, such as thalidomide (Delahunt and Lassen, 1964; Wilson and Gavan, 1967), triazene (Frank et al, 1989; Louryan et al, 1995; Glineur et al, 1999), cocaine (Webster and Brown‐Woodman, 1990), and salicylates (Warkany and Takacs, 1959; Kimmel et al, 1971; Khera, 1976). In humans, associations have been reported for a variety of vasoactive agents, including thalidomide (Brent and Holmes, 1988), misoprostol (Orioli and Castilla, 2000; Vargas et al, 2000), cigarette smoking (Goldbaum et al, 1990; Haddow et al, 1993; Czeizel et al, 1994; Kallen, 1997a, 1997b; Skelly et al, 2002) cocaine (Hoyme et al, 1990; Addis et al, 2001), aspirin (Kozer et al, 2002), and ibuprofen (Werler et al, 2004).…”
Section: Vascular Disruptionmentioning
confidence: 99%
“…Micrognathism, a permanent structural alteration, is a teratogenic effect. In rat embryos, DMPT-induced micrognathism is produced at a very high incidence (18) and is minimally affected by phase specificity (Frank, unpublished data (6,7). Odontomas are uncommon lesions in laboratory animals (17).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…From gestation day 11 through gestation day 15, teratogenic targets of DMPT include the central nervous system, limbs, and craniofacial region. The mandible is most commonly affected by DMPT, and this remarkable organotropism makes DMPT an excellent experimental model of micrognathism (18). Classical alkylating teratogens exhibit marked phase specificity, and administration of these agents on gestation days [12][13][14][15] should induce a high percentage of urogenital malformations (29).…”
Section: Introductionmentioning
confidence: 99%
“…Frank et al .,[23] described the effects of 30 mg/kg of 3.3 dimethyl-1-phenyl triazene administered on day 12 of gestation in the rat. At external examination, they found 82% of cases with micrognathia and 100% of embryos with CP.…”
Section: Formation Of Orofacial Cleftingmentioning
confidence: 99%